PHYSICAL EUSTRESSORS AS POTENTIAL TOOLS TO IMPROVE CROP STRESS TOLERANCE (REVIEW) - Oleg N. Bakhchevnikov; Sergey V. Braginets; Nina S. Kravchenko; Viktor I. Pakhomov (Siberian Journal of Life Sciences and Agriculture, 2023)
Background. The processes occurring in plants and their seeds under stress, as well as the defense mechanisms used by plants under stress, are poorly understood, which makes it impossible to use them to increase yields.